KOMPOSISI SEDIMEN BAGIAN TIMUR SELAT RUPAT PROVINSI RIAU - Sihombing, Tumpal; Rifardi, Rifardi (Jurnal Perikanan dan Kelautan, 2014)
The research was conducted in June 2013 in Rupat Starait waters with the aim to deter-mine the constituent materials in the sediment. The Eckman Grab was used to take samples and than the sediment was analyzed to determine the composition and content of organic mat-ter. The results showed that the composition of the sediment composed of lithogenous and biogenous. Lithogenous composition especially in waters and rocks dominating presence even-ly at each station. The highest composition found in a location close to the mainland and one of the areas that get the first time the influence of the tide, from the Strait of Malacca and the flow from Strait of Bengkalis. Lithogenous lowest percentage was found in areas close to the mangrove area whre the station had high composition of litter biogenous. While the station containing the lowest organic matter was the station near the strait of Malacca. Mean while the station closed masjid river and Dumai river containing organic matter was high due to the flow of the river carrying a high content of organic materials.